Synthesis of 2,3-Dihydro-4-pyridones Using HClO4-SiO2 or NaHSO4-SiO2 as an Efficient Heterogeneous Catalyst - Wu, Liqiang; Yang, Limin; Yan, Fulin (Asian Journal of Chemistry, 2010)
A simple and efficient synthesis of 2,3-dihydro-4-pyridones has been accomplished by threecomponent condensation reactions of Danishefsky's diene with aldehydes and amines in the presence of HClO4-SiO2 or NaHSO4-SiO2.